Interactive Pictorial Story as Learning Media for Third Grade Students - Nurul Inayah; Andarini Permata Cahyaningtyas; Rida Fironika Kusumadewi (Profesi Pendidikan Dasar, 2021)
This study aims to develop an interactive pictorial story as a learning media on theme 2 Loving Plants and Animals and to determine its feasibility, practicality, and effectiveness. This study uses the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). In this study, the results obtained include: (1) The feasibility of the media obtained from the validation results by 5 validators obtained an average of 0.83 for content quality indicators and objectives, instructional quality indicators obtained an average of 0.84 and technical quality indicators obtained an average of 0.83. The average number of all indicators is 0.83 with the category "very valid". (2) The practicality of the media obtained a percentage of 98% in the "very feasible" category of teacher responses and 96% in the "very feasible" category of student responses. (3) The effectiveness is calculated by using the gain test of 0.56 indicating an increase in student learning outcomes in the "medium" category. The result of this research can be a reference to understand that an interactive pictorial story will be a big help for teachers in conducting an interesting teaching and learning process, especially during this pandemic. The pictorial story was created in an interactive format, so students can learn the material in a fun and interesting way. Besides, in this outbreak, students need to have a technology-based learning resource other than their school books so they can study independently.